Genome Sequence of Diplorickettsia massiliensis, an Emerging Ixodes ricinus-Associated Human Pathogen - Mathew, Mano J. (American Society for Microbiology, 2012)
Diplorickettsia massiliensis is a gammaproteobacterium in the order Legionellales and an agent of tick-borne infection. We sequenced the genome from strain 20B, isolated from an Ixodes ricinus tick. The genome consists of a 1,727,973-bp chromosome but no plasmid and includes 2,269 protein-coding genes and 42 RNA genes, including 3 rRNA genes.